2020
DOI: 10.1038/s41598-020-60765-1
|View full text |Cite
|
Sign up to set email alerts
|

Modification of radiosensitivity by Curcumin in human pancreatic cancer cell lines

Abstract: Pancreatic cancer is one of the most aggressive malignancies and is characterized by a low 5-year survival rate, a broad genetic diversity and a high resistance to conventional therapies. As a result, novel therapeutic agents to improve the current situation are needed urgently. Curcumin, a polyphenolic colorant derived from Curcuma longa root, showed pleiotropic influences on cellular pathways in vitro and amongst others anti-cancer properties including sensitization of tumor cells to chemo-and radiation-ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 57 publications
0
21
0
2
Order By: Relevance
“…In recent years, more and more researchers reported that active compounds from Chinese herbs such as curcumin, 69–71 resveratrol, 72–74 dihydroartemisinin 75–77 and paclitaxel, 78–80 could enhance tumor radiotherapy sensitivity ( Figure 2 ). Curcumin is a polyphenolic active compound extracted from turmeric.…”
Section: Small Moleculesmentioning
confidence: 99%
“…In recent years, more and more researchers reported that active compounds from Chinese herbs such as curcumin, 69–71 resveratrol, 72–74 dihydroartemisinin 75–77 and paclitaxel, 78–80 could enhance tumor radiotherapy sensitivity ( Figure 2 ). Curcumin is a polyphenolic active compound extracted from turmeric.…”
Section: Small Moleculesmentioning
confidence: 99%
“…PANC-1 cells were radiosensitized after 24 h of incubation with 10 (4 Gy: p = 0.0048, 6 Gy: p = 0.0096) or 12 µm of Curcumin (4 Gy: p = 0.0028, 6 Gy p = 0.0003, 8 Gy: p = 0.00070) whereas MiaPaCa-2 cells showed no significant radiosensitization. Furthermore, curcumin increased radiation induced apoptosis in both cells lines after 8 Gy exposure (PANC-1: p = 0.0174, MiaPaCa-2: p = 0.0043) [74]. This research also identified curcumin induced DNA damage via γ-H2AX evaluation and radiation induced G2/M arrest [74].…”
Section: Natural Radiosensistisersmentioning
confidence: 55%
“…Furthermore, curcumin increased radiation induced apoptosis in both cells lines after 8 Gy exposure (PANC-1: p = 0.0174, MiaPaCa-2: p = 0.0043) [74]. This research also identified curcumin induced DNA damage via γ-H2AX evaluation and radiation induced G2/M arrest [74].…”
Section: Natural Radiosensistisersmentioning
confidence: 55%
See 1 more Smart Citation
“…A limiting factor that could hinder the efficacy of this treatment modality in cancer patients is the low bioavailability and chemical instability of Curcumin (144). Indeed, obtaining a blood concentration of Curcumin comparable to the ones used in in vitro studies represents a great challenge that could be overcome improving the absorption through coating it in nanoparticles, liposomes or phospholipid complexes (145,146). For what concerns nanoparticles, a phase II clinical trial in which Nanocurcumin is coupled to Radiotherapy (RT) is ongoing in prostate cancer patients (ClinicalTrials.gov number, NCT02724618), and it will hopefully provide new insights on the potential advantages given by a different Curcumin delivery.…”
Section: Pathways Involved In Nf-kb-mediated Radioresistancementioning
confidence: 99%